IMPLEMENTATION OF ANALYTIC NETWORK PROCESS (ANP) METHOD IN THE ORDER OF SELECTING THE ALTERNATIVE SUBMARINE OF THE INDONESIAN NAVY - Dani Hutabarat; Ahmadi Ahmadi; Avando Bastari (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT This paper describes the application of the Analytic Network Process (ANP) method in submarine selection as one of the defence equipment with very strategic value, the procurement of submarines is directed at realizing a deterrence strategy and a strategy of balancing with state actors that have the potential to threaten the sovereignty of the Republic of Indonesia. Apart from threats, the procurement of submarines also considers the geographical constellation of the Republic of Indonesia and the government's wishes, such as the interest of the minister of defence during visits to countries that offer their submarines. Therefore, before the procurement, an analysis was made in terms of the selection of submarine alternatives, both analysis of information and identification of various essential and interrelated requirements regarding data from submarine alternatives that would later be selected. In addition to other options, it is hoped that the main criteria for selecting submarines will be known. In submarine procurement decisions, where the existing problems cannot be arranged in a hierarchical form because it involves the interaction and dependence of the higher-level elements on the lower-level elements. Therefore, in this study the ANP method is used, which can accommodate the linkages between criteria or alternatives. The results obtained are the most substantial alternative priority weight on the S-Class submarine made by P-Country of 0.383283. While the results of the importance of the criteria are sequential starting from the sensor criteria of 0.125127, Threat 0.089076, Neighbors power state 0.080153, Geographical conditions 0.75735, Interoperability 0.071664, Weaponry 0.068672, Navigation 0.047301, Platform 0.044235 and finally Machinery 0.020580. Keywords: ANP method, Submarine, Alternative priority.